2021
DOI: 10.1021/acs.iecr.1c00928
|View full text |Cite
|
Sign up to set email alerts
|

Two-Fluid Simulation of a Three-Dimensional Spout-Fluid Bed: Flow Structures, Regimes, and Insight into the Mechanism of Particle–Particle Momentum Transfer

Abstract: Spout-fluid beds are widely used in the process industry due to their facilitation of an efficient contact between particles and gas. In this paper, a two-fluid model (TFM) is set up to reproduce the various flow structures encountered during spout-fluid bed operation. The effects of normal restitution model and gas–solid drag model are assessed by comparing simulation results with the experimental and discrete particle modeling (DPM) data of Link et al. [Link et al. Chem. Eng. Sci. 2005, 60, 3425–3442; Link e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Interphase drag models Bed type Guo et al (2021) (Guo et al, 2021) Gidaspow (Gidaspow, 1994) (TFM and CFD-DEM), Single-spout Beetstra et al (Beetstra et al, 2007), Koch and Hill (Hill et al, 2001) and O'Brien, 1987) Chen et al (2019) (Chen et al, 2019) Syamlal O'Brien (Syamlal and O'Brien, 1987) (TFM) and Multiple-spout DeFelice (Di Felice, 1994) (CFD-DEM) Almohammed et al (2014) (Almohammed et al, 2014) Gidaspow (Gidaspow, 1994), Wen and Yu (Wen, 1966), Single-spout Syamlal O'Brien (Syamlal and O'Brien, 1987) (TFM) and Koch and Hill (Hill et al, 2001 closures of frictional solids stresses in the literature (Zhao et al, 2021;Guo et al, 2021;Wang et al, 2014;Zhao et al, 2022) such as Johnson and Jackson (Johnson and Jackson, 1987), Srivastava and Sundaresan (Srivastava and Sundaresan, 2003) and Syamlal et al (Syamlal et al, 1993) strongly depend on empirical parameter of minimum solids volume fraction, a min s (the point, where frictional stresses become non-negligible), and are monotonically increasing functions with increasing solids volume fraction. In addition, particle-wall impacts in these TFM simulations are resolved with Johnson and Jackson (Johnson and Jackson, 1987) boundary condition.…”
Section: Authormentioning
confidence: 99%
See 2 more Smart Citations
“…Interphase drag models Bed type Guo et al (2021) (Guo et al, 2021) Gidaspow (Gidaspow, 1994) (TFM and CFD-DEM), Single-spout Beetstra et al (Beetstra et al, 2007), Koch and Hill (Hill et al, 2001) and O'Brien, 1987) Chen et al (2019) (Chen et al, 2019) Syamlal O'Brien (Syamlal and O'Brien, 1987) (TFM) and Multiple-spout DeFelice (Di Felice, 1994) (CFD-DEM) Almohammed et al (2014) (Almohammed et al, 2014) Gidaspow (Gidaspow, 1994), Wen and Yu (Wen, 1966), Single-spout Syamlal O'Brien (Syamlal and O'Brien, 1987) (TFM) and Koch and Hill (Hill et al, 2001 closures of frictional solids stresses in the literature (Zhao et al, 2021;Guo et al, 2021;Wang et al, 2014;Zhao et al, 2022) such as Johnson and Jackson (Johnson and Jackson, 1987), Srivastava and Sundaresan (Srivastava and Sundaresan, 2003) and Syamlal et al (Syamlal et al, 1993) strongly depend on empirical parameter of minimum solids volume fraction, a min s (the point, where frictional stresses become non-negligible), and are monotonically increasing functions with increasing solids volume fraction. In addition, particle-wall impacts in these TFM simulations are resolved with Johnson and Jackson (Johnson and Jackson, 1987) boundary condition.…”
Section: Authormentioning
confidence: 99%
“…In addition, the validity of the derived constitutive closures for particle-particle interactions and particle-wall boundary conditions in TFM approach can be examined in modelling of the spout fluidized beds. There are extensive studies in the literature on the modelling of the spout fluidized beds with either CFD-DEM (Jajcevic et al, 2013;Link et al, 2005;Link et al, 2007;Link et al, 2008;van Buijtenen et al, 2009;Buijtenen et al, 2012;van Buijtenen et al, 2011;Yang et al, 2019;Yue et al, 2019;Yue et al, 2021) or TFM (Zhao et al, 2021;Wang et al, 2014;Wu et al, yyyy;Zhao et al, 2016;Zhao et al, 2022) approaches. For instance, Link et al (Link et al, 2005) investigated the CFD-DEM simulations of the single-spout fluidized beds in different flow regimes, and van Buijtenen et al (van Buijtenen et al, 2011) studied different flow regimes in the multiple-spout fluidized beds via experiments and CFD-DEM simulations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al studied 3D hydrodynamic behaviors of a spouted bed under swirling flow. Zhao et al reported that the application of an effective restitution coefficient and drag model in TFM method could improve the accuracy of prediction significantly in a 3D spouted fluidized bed. Furthermore, they simulated and studied the hydrodynamics and heat transfer of a 3D spouted–fluidized bed with single, double, and triple chambers …”
Section: Introductionmentioning
confidence: 99%